Analysis of quartz LM-OSL curves - Choi, J. H.; Duller, G. A. T.; Wintle, A. G. (Ancient TL, 2006)
Measurement of the optically stimulated luminescence signal during linear ramping of the stimulation power (LM-OSL) is a useful and efficient method for separating constituent OSL components, and for detailed investigation of the luminescence properties of each component. However, the practical procedures for the analysis of the quartz LM-OSL signal have been largely ambiguous in previous publications. In this study, we discuss various aspects of the analysis of quartz LM-OSL curves. This includes the measurement of background count rate, deconvolution of the LM-OSL curves using commercially available software, derivation of detrapping probabilities from the fitting results, and the identification and characterisation of each OSL component based upon the photoionisation cross-sections derived from these values.